Microplastic contamination of Seawater and Fish samples from Bhaucha Dhakka and Versova Beach on the Mumbai Coast - Ayushi, Singh; Meghana Bhushan, Talpade (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
Plastics gained prominence in enhancing human lives due to their long durability, good mechanical qualities, weather resistance, and extended service life. The prevalence of microplastics in the environment is well recognized, but the deep extent of its impact on ecosystems is unknown. This study investigates the prevalence of microplastics in seawater and three species (Bombay duck, Silver Pomfret, and Indian prawn) of commercially available marine fish from the Mumbai suburbs. The investigation found microplastics in both water and fish samples, with an average concentration of 20 ± 14.8 MPs/L and 42 ± 14.8 MPs/L in two water samples from Versova Beach and Bhaucha Dhakka selected for the study. And 70 ± 10, 36 ± 08, and 23 ± 09 MPs/L respectively in three fish species. The highest concentrations were found in water samples from Bhaucha Dhakka and Bombay duck (Harpadon nehereus) from Bhaucha Dhakka. The discovery of microplastics in fish tissues raises concerns about their potentially harmful impact on fish health and the implications for human consumption. Moreover, ongoing construction and redevelopment projects in and around the Mumbai region are major sources of pollution in nearby water bodies, which may also be linked to microplastic contamination. More research and animal model studies will be critical in filling the knowledge gap on the impacts of microplastics on human health.